The Formation of the Greek Image of Northerners’ Religions: A Diachronic Account - Lampinen, Antti (Suomen Ateenan Instituutin Säätiö, 2026)
This chapter seeks to provide a diachronic perspective on the development of the Greek way of imagining northern peoples’ religious cultures and attitudes. The interactions between the Greek tradition and the Latin one will form a specific focus. Primarily, the discussion will deal with sources ranging from the Classical Period to the second century CE, the era of the Second Sophistic in the Greek culture of the Roman empire. The fascinating sources of Late Antiquity and the Byzantine Middle Ages are, for the purposes of this chapter, largely left out, as they would deserve a dedicated study of their own. I will also range on a few occasions beyond the Greek-language sources. In the Imperial Era, the influence of the Greek ideological and literary currents was felt in the wider society of the Roman empire: indeed, as we shall see, it was not limited only to Latin literature, either. While the focus will be on giving a synoptic overview of the shaping of the tradition, some less-studied texts are investigated at more depth.
Marking the North. The Greek Tradition and Its Influence in the Roman Period